2013
DOI: 10.1093/aobpla/plt024
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of purple saxifrage (Saxifraga oppositifolia) in the high Arctic archipelago of Svalbard

Abstract: Using DNA markers and sequencing we investigated patterns of genetic variability in purple saxifrage, Saxifraga oppositifolia in the isolated Arctic Svalbard archipelago. Purple saxifrage is a circumpolar, ecologically and morphologically variable species with a wide range of habitats. Population genetic structures showed that both genetic variation and differentiation levels are modest, outcrossing is the main mating system, and dispersal and gene flow are important, likely accountable to strong winds and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Moreover, these levels were also comparable to limited number of populations studied earlier in case of B. ciliata (Tiwari et al 2015). At population level, B. ciliata revealed higher levels of genetic diversity than the diversity found in Saxifraga paniculata using RAPD (Reisch et al 2003) and Kirengeshoma palmata (family Hydrangeaceae) using allozyme markers (Chang et al 2007), but these levels were lower than diversity found in Saxifraga oppositifolia (Pietiläinen and Korpelainen 2013) and S. granulata (van der Meer and Jacquemyn 2015) with polymorphic microsatellite markers. At population level, B. ciliata showed higher percentage of polymorphism than in Saxifraga paniculata, but at species level, polymorphism was comparatively low.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, these levels were also comparable to limited number of populations studied earlier in case of B. ciliata (Tiwari et al 2015). At population level, B. ciliata revealed higher levels of genetic diversity than the diversity found in Saxifraga paniculata using RAPD (Reisch et al 2003) and Kirengeshoma palmata (family Hydrangeaceae) using allozyme markers (Chang et al 2007), but these levels were lower than diversity found in Saxifraga oppositifolia (Pietiläinen and Korpelainen 2013) and S. granulata (van der Meer and Jacquemyn 2015) with polymorphic microsatellite markers. At population level, B. ciliata showed higher percentage of polymorphism than in Saxifraga paniculata, but at species level, polymorphism was comparatively low.…”
Section: Discussionsupporting
confidence: 81%
“…Now-a-days genetic markers are considered a valuable source for identification of potential genotypes for breeding purpose by studying genetic diversity within and among the species. There are only limited information available on genetic variability and population structure of species of the family Saxifragaceae, based on RAPD (Reisch et al 2003), allozyme (Chang et al 2007), microsatellite, internal transcribed spacer and chloroplast markers (Pietiläinen and Korpelainen 2013;van deer Meer and Jacquemyn 2015;Gao et al 2017). Moreover, an earlier study specific to B. ciliata was restricted to Western Himalayas representing relatively a limited geographic area (Tiwari et al 2015), though the species has a widespread distribution in IHR.…”
Section: Introductionmentioning
confidence: 99%
“…below 1%), interestingly, a very high abundance of reads was found in multiple datasets from rhizosphere of Saxifraga oppositifolia (up to 41%) , collected in Spitsbergen (Norway) and a dataset from roots and leaves of Boechera stricta (10%) collected in the Rocky Mountains (USA). Both are perennial herbs native to Arctic-Alpine regions (Saxifraga oppositifolia) [89] and montane regions of western North America (Boechera stricta) [61]. The high abundance of Chioneia species present in the proximity or on these plants may thus indicate a close cooperation between them.…”
Section: Environmental Distribution Of Chioneia Gennovmentioning
confidence: 99%